STOPP/START version 2--development of software applications: easier said than done? - ANRYS, PAULINE; BOLAND, BENOÎT; DEGRYSE, JEAN-MARIE; DE LEPELEIRE, JAN; PETROVIC, MIRKO; MARIEN, SOPHIE; DALLEUR, OLIVIA; STRAUVEN, GOEDELE; FOULON, VEERLE; SPINEWINE, ANNE (Age & Ageing, 2016)
Explicit criteria, such as the STOPP/START criteria, are increasingly used both in clinical practice and in research to identify potentially inappropriate prescribing in older people. In an article on the STOPP/START criteria version 2, O'Mahony et al. have pointed out the advantages of developing computerised criteria. Both clinical decision support systems to support healthcare professionals and software applications to automatically detect inappropriate prescribing in research studies can be developed. In the process of developing such tools, difficulties may occur. In the context of a research study, we have developed an algorithm to automatically apply STOPP/START criteria version 2 to our research database. We comment in this paper on different kinds of difficulties encountered and make suggestions that could be taken into account when developing the next version of the criteria.